ACCELARATING THE STUDENTS' FREQUENCY WORD FOR BASIC CONVERSATION BY GIVING A WEEKLY ACHIVABLE TARGET OF ENGLISH VOCABULARY AT JUNIOR HIGH SCHOOL 1 BONTOMMARANNU - Masitah; Abdul, Nurdevi bte; Hafid, Hilda (English Language Teaching Methodology, 2023)
This research is aimed to To find out many Action verbs and Phrasal Verbs are achivable by first grade students’ in a week at Junior High School. The research applied pre-experimental method with one group pre-test post-test design and the data were collected by giving pre-test, treatment and post-test. the sample of the research was VII 8 at Junior High School 1 Bontomarannu which consisted of 16 students. The population of this study was the first grade at  Junior High School 1 Bontomarannu which consisted of 296 students in the academic year of 2021/2022. The sample was taken by cluster random sampling technique to select the sample of the research. The technique used for obtaining data was vocabulary test words. The research findings showed that the mean score of students vocabulary in action verb was proved by post-test 76.87 it was higher than the mean score of the students in pre-test 41.25. Mean score of the students vocabulary in phrasal verb was proved by pre-test 42.87 and post-test 76.25. and the hypothesis t-test value was 4.01. it means that Ha was accepted. In other words, vocabulary by giving a weekly achivable target was very good in enhance the students vocabulary especially in action verb and phrasal verb.